2013
DOI: 10.3109/09687637.2013.765386
|View full text |Cite
|
Sign up to set email alerts
|

The role of alcohol price in young adult drinking cultures in Scotland

Abstract: Minimum Unit Pricing (MUP) is one of the Scottish Government's key policy options to reduce alcohol consumption and related harm. Although strongly evidenced for efficacy in reducing headline population level consumption, efficacy in changing the role of alcohol in Scottish culture is unknown. Questions remain as to how MUP will play across population subgroups with different sensitivities to price. In this paper we explore the views of the young adult population and situate the influence of price paid for alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…Available socio-demographic and health-related significant risk factors could not explain the negative association between being NEET and heavy drinking when considering all NEETs. For example, although some previous research has reported lower levels of alcohol consumption amongst young mothers [ 16 , 49 ] and young people who are disabled [ 50 ], adjusting for gender did not alter the effect of NEET status on heavy drinking and limiting long-term illness was not significantly associated with heavy drinking in this study. However, this study did not control for whether respondents had children.…”
Section: Discussioncontrasting
confidence: 87%
“…Available socio-demographic and health-related significant risk factors could not explain the negative association between being NEET and heavy drinking when considering all NEETs. For example, although some previous research has reported lower levels of alcohol consumption amongst young mothers [ 16 , 49 ] and young people who are disabled [ 50 ], adjusting for gender did not alter the effect of NEET status on heavy drinking and limiting long-term illness was not significantly associated with heavy drinking in this study. However, this study did not control for whether respondents had children.…”
Section: Discussioncontrasting
confidence: 87%
“…Previous authors have reported that price and affordability might not be as effective at reducing drinking in young people as in adults, or as compared to other strategies such as point of sale or offer restrictions (Meier et al ., 2009). As work in Scotland has concluded, young adults are not a homogeneous group in relation to price sensitivity, and considerations about the price of alcohol compete with non-financial considerations such as cultural norms regarding drinking activity (Seaman et al ., 2013). Eleven (of 14) placement studies reported mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…The increase is, however, not equally distributed, with the impact of adjustment generally decreasing with age in both males and females and, for instance, increasing units/week in 16- to 24-year-old females by more than 50% (Table 4 ). Younger drinkers often have expendable income and opportunity to incorporate weekly binges and increased alcohol consumption with celebrations of frequent special occasions [ 35 ]. Thus, for the highest risk drinkers aged 25 to 34, accounting for atypical and special occasion drinking was estimated to increase typical weekly consumption by around 18 units (Additional file 2 : Table S2).…”
Section: Discussionmentioning
confidence: 99%